Anti-inflammatory and anti-hyperalgesic acitivities of Acanthopanax trifoliatus (L.) Merr leaves - Abd Hamid @ Abdul Razak, Roslida; Teoh, Hui Kee; Othman, Fezah (Wolters Kluwer - Medknow Publications, 2013)
Context: Acanthopanax trifoliatus is a ginseng-like plant, which has been widely used to treat various diseases including inflammatory-related diseases. Aims: The present study has been designed to investigate the anti-inflammatory and anti-hyperalgesic effects of various fractions of Acanthopanax trifoliatus leaves ethanolic extract in rats. Materials and Methods: Anti-inflammatory activity was studied by using carrageenan-induced edema on rat paw whilst anti-hyperalgesic was assessed by using carrageenan-evoked thermal hyperalgesia on plantar test. Statistical Analysis Used: Data were analyzed using Student t-test to compare with control.Multiple comparisons for difference between control and extract-treated groups were evaluated by Tukey HSD (Honestly Significant Difference) test. P values less than 0.05 (P < 0.05) is considered significant. Results: Among three different fractions i.e., hexane, dichloromethane, and methanol tested, methanolic fraction displayed the most potent fraction amongst those three. It gave significant anti-inflammatory effect at highest dose, 500 mg/kg, with 77.24% of inhibition. Whilst for anti-hyperalgesic activity, methanolic fraction showed the highest efficacy at 375 mg/kg. Administration of methanolic fraction of Acanthopanax trifoliatus inhibited paw edema in a dose- dependent manner. The inhibition for both activities might be due to possible composition of polar compounds, which are flavonoids and phenolics content. Conclusions: Methanol fraction of Acanthopanax trifoliatus leaves has potential effect as anti-inflammatory and anti-hyperalgesia in acute inflammation model.